Using Self-Portrait Series and Video in Teaching Writing to Students with Low and High Motivation - Ningrum, Rena Listya; Hartono, Rudi (Universitas Negeri Semarang, 2018)
Taking selfie and recording video are two activities that are very usual nowadays. Students use and then upload them in their social media with some caption based to their activities or experience. This is an experimental research with 2x2 factorial design aimed to analyse the use of selfie series and video in writing recount text between students with high and low motivation. The sample of the study was eighth graders of SMP N 1 Kesesi in the academic year 2015/2016. There were two classes, selfie series was used in experimental group and video was used in control group which each class consist of 35 students. The result of the study shows that selfie series is effective with high motivation and low motivation. Video is effective with high motivation and low motivation but the score that video had gotten was not as higher as selfie series. To see the comparison, the use of selfie series is more effective to students with high motivationthan video. Video is more effective to students with low motivation than selfie series. But, there is no any interaction between the use of selfie series and and video to students’ motivation. To conclude, selfie series is effective, but the students’ motivations have no effect on the result.